Ionic Liquids as Unforeseen Assets to Fight Life-Threatening Mycotic Diseases - Hartmann, Diego O.; Petkovic, Marija; Silva Pereira, Cristina (Frontiers in Microbiology, 2016)
Ionic liquids discovery has celebrated 100 years. They consist solely of ions, one of which is typically organic and asymmetrical. Remarkable physical and chemical properties stirred their use as alternative solvents in many chemical processes. The recent demonstration of their occurrence in nature might boost their interest in biological sciences. In the search of mechanistic understandings of ionic liquids’ ecotoxicological impacts in fungi, we have analyzed the proteome, transcriptome and metabolome responses to this chemical stress. Data illuminated new hypotheses that altered our research path – exploit ionic liquids as tools for the discovery of pathways and metabolites that may impact fungal development and pathogenicity. As we get closer to solve the primary effects of each ionic liquid family and their specific gene targets, the vision of developing antifungal ionic liquids and/or materials, by taking advantage of elegant progresses in this field, might become a reality. Task-designed formulations may improve the performance of conventional antifungal drugs, build functional coatings for reducing allergens production, or aid in the recovery of antifungal plant polymers. The frontier research in this cross-disciplinary field may provide us unforeseen means to address the global concern of mycotic diseases. Pathogenic and opportunistic fungi are responsible for numerous infections, killing annually nearly 1.5 million immunocompromised individuals worldwide, a similar rate to malaria or tuberculosis. This perspective will review our major findings and current hypotheses, contextualizing how they might bring us closer to efficient strategies to prevent and fight mycotic diseases.